2019
DOI: 10.1111/jace.16712
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle assessment of functional materials and devices: Opportunities, challenges, and current and future trends

Abstract: Functional ceramics such as piezoelectrics, thermoelectrics, magnetic materials, ionic conductors, and semiconductors are opening new frontiers that underpin numerous aspects of modern life. This widespread usage comes with a responsibility to understand what impact their mass production has on the environment. Life‐cycle assessment (LCA) is a tool employed for the identification of sustainable materials pathways through the consideration of environmental burdens of materials both during fabrication and as a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 97 publications
(386 reference statements)
0
13
0
Order By: Relevance
“…This concerns the environmental impacts (e.g., human toxicity, global warming, and eutrophication) associated with the sourcing of the base materials used in a given EH and its manufacturing process, use, and decommissioning at the end‐of‐life. [ 58 ] Important aspects that may ensure the environmental sustainability of a given EH technology concern the use of Earth‐abundant and nontoxic base materials as well as low‐energy manufacturing processes. It is especially important to use benign materials for the fabrication of EHs for the IoT because a wide range of IoT nodes are to be placed in daily objects and environments, hence in the vicinity of human end‐users.…”
Section: The Need For Sustainable and Autonomous Iot Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…This concerns the environmental impacts (e.g., human toxicity, global warming, and eutrophication) associated with the sourcing of the base materials used in a given EH and its manufacturing process, use, and decommissioning at the end‐of‐life. [ 58 ] Important aspects that may ensure the environmental sustainability of a given EH technology concern the use of Earth‐abundant and nontoxic base materials as well as low‐energy manufacturing processes. It is especially important to use benign materials for the fabrication of EHs for the IoT because a wide range of IoT nodes are to be placed in daily objects and environments, hence in the vicinity of human end‐users.…”
Section: The Need For Sustainable and Autonomous Iot Devicesmentioning
confidence: 99%
“…This concerns the environmental impacts (e.g., human toxicity, global warming, and eutrophication) associated with the sourcing of the base materials used in a given EH and its manufacturing process, use, and decommissioning at the end-of-life. [58] Important aspects that may ensure the environmental sustainability of a given EH technology concern the use of Earth-abundant and nontoxic base materials as well as low-energy manufacturing processes.…”
Section: Environmental Sustainabilitymentioning
confidence: 99%
“…[ 116 ] In turn, the recovery from WEEE is considered extremely challenging due the small mass concentration, making its recovery economically unfeasible. [ 171 ] Meanwhile, an LCA study revealed that the mining process of tantalum (Ta) generates more than 85% of the total environmental impact in 13 categories, [ 172 ] and the supply in capacitors for consumer electronics alone accounts for around 53% of the global consumption of tantalum. [ 166 ] Consequently, in the early 2000s, tantalum (Ta) prices rose, boosting niobium in electronic capacitors as a more common substitution.…”
Section: Materials Used In Electronicsmentioning
confidence: 99%
“…[ 116,155 ] Additionally, Smith et al. [ 172 ] concluded that multilayer ceramic capacitor (MLCC) technology has a positive environmental impact in comparison to tantalum technologies.…”
Section: Materials Used In Electronicsmentioning
confidence: 99%
See 1 more Smart Citation